Aspartic acid based metal–organic frameworks with dual function of NADH peroxidase and glycerol dehydrogenase-mimicking activities. (6th October 2022) - Liu, Shuli; Wu, Xiaoling; Xiong, Jun; Yuan, Xin; Zong, Min-Hua; Lou, Wen-Yong
Abstract : CuAsp with a fiber-like structure exhibited both NADH peroxidase- and glycerol dehydrogenase (GlyDH)-mimetic activities. Abstract : Enzymatic cofactor regeneration is of significant importance and highly desired for tremendous biocatalytic processes, which is hindered by fragility intrinsic to natural enzymes. Herein, we report a copper aspartic acid (CuAsp) metal–organic framework (MOF) with a fiber structure exhibiting both NADH peroxidase- and glycerol dehydrogenase (GlyDH)-mimicking activities. The growth mechanism of CuAsp was investigated by changing the functional groups of ligands, which demonstrated that the amino group and two carboxylate groups in aspartic acid were all involved in the formation of MOFs. The CuAsp MOF displayed high NADH peroxidase mimicking activity within a wide range of pH and temperature. A cofactor total turnover number (TTN) of up to 17 500 was obtained in a typical model reaction of glucose dehydrogenase-catalyzed oxidation of glucose. More interestingly, CuAsp exhibited glycerol dehydrogenase (GlyDH)-mimicking activity and showed higher catalytic efficiency (with k cat / K m of 14.42 mL g −1 min −1 ) than its native counterpart (with k cat / K m of 2.40 mL g −1 min −1 ). As a proof of concept, CuAsp with the dual function of NADH peroxidase and GlyDH-mimicking activities was used to catalyze the transformation of glycerol to 1, 3-dihydroxyacetone (DHA). Besides, free GlyDH was encapsulated into CuAsp via a facile self-assembly process, which enabled the synergistic biosynthesis of DHA. This study may provide new insights into amino acid-based MOFs and suggest the potential of multifunctional nanozymes in the application of biocatalysis and biosensing.